Impact of feed restriction on health, digestion and faecal microbiota of growing pigs housed in good or poor hygiene conditions. (25th June 2014) - Le Floc'h, N.; Knudsen, C.; Gidenne, T.; Montagne, L.; Merlot, E.; Zemb, O.
<x content-type="archive" xml:space="preserve">Abstract</x> Feed restriction could be a relevant strategy to preserve gut health, reduce systemic inflammatory response and finally limit antibiotic use. This study assessed the effect of feed restriction on growing pigs submitted to a moderate inflammatory challenge induced by the degradation of the environmental hygiene that is known to alter growth rate. The experiment was run on 80 pigs selected at 7 weeks of age according to a 2×2 factorial design: two feeding levels, ad libitum (AL) and feed restricted (FR) at 60% of AL, and two conditions of environmental hygiene, clean and dirty. Pigs were housed individually throughout the experiment. From 61 to 68 days of age (day 0 to 7), pigs were housed in a post weaning unit and feed restriction was applied to half of the pigs from day 0 to day 29. At 68 days of age (day 7 of the experiment), pigs were transferred in a growing unit where half of FR and half of AL pigs were housed in a dirty environment (poor hygiene) and the other half in a clean environment (good hygiene) until day 42. Growth performance was recorded weekly. Blood and faeces samples were collected to measure indicators of inflammation, nutrient digestibility and microbiota composition. Faecal consistency was monitored daily to detect diarrhoeas. Feed restriction decreased daily weight gain (−35% to −50%, P<0.001), increased the feed conversion ratio (+15%, P<0.001) and CP digestibility (+3%, P<0.05) and reduced the occurrence of diarrhoeas irrespective of hygiene conditions. Poor hygiene conditions decreased growth performance (−20%, P<0.05) and total tract digestibility of all nutrients (P<0.001). Haptoglobin (+50%) concentrations and lymphocyte (+10%) and granulocyte (+40%) numbers were higher in poor hygiene conditions (P<0.05), confirming that the model was effective to induce a systemic inflammatory response. Both feed restriction and hygiene modified the profile of the faecal microbiota. In this study, feed restriction did not reduce the systemic inflammatory response caused by poor hygiene conditions despite the limitation of the occurrence of digestive disorders. However, our study opens discussions regarding the impact of hygiene and feed restriction on gut microbial communities and digestive health.